QUESTIONS REGARDING THE APPOINTMENT AND EXECUTION OF FORENSIC EXAMINATIONS IN THE PROCESS OF JUDICIAL PROCEEDINGS - Rakhimova Ulzana (Scholar Express Journals, 2024)
The article examines the procedural order of conducting forensic examinations during judicial investigation.
Keywords: Evidence; Expertise; Court